Lippia alba—a potential bioresource for the management of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Biswas, Shreosi; Kundu, Aditi; Suby, S. B.; Kushwah, Abran Singh; Patanjali, Neeraj; Shasany, Ajit Kumar; Verma, Rajesh; Saha, Supradip; Mandal, Abhishek; Banerjee, Tirthankar; Kumar, Anil; Singh, Anupama (Frontiers in Plant Science, 2024)
Fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith), a threat to maize production systems, is a highly polyphagous pest of global significance. There is no registered bioinsecticide of botanical origin to provide green remedy against this pest of concern. The present study reports for the first time the potency of the polar and non-polar bioinsecticidal leads sourced from Lippia alba (Mill.) N.E. Br. leaves. Shade-dried leaves of L. alba were extracted and evaluated;with various solvents and based on preliminary bioassay the ethyl acetate leaf extract of L. alba (LEAE) was found to be the most potent against fall armyworm (FAW) in the in-vitro and in-vivo studies. Ultra Performance Liquid Chromatography-Quadrupole-Time of Flight-Mass Spectrometric (UPLC-QTOF-MS) analysis of LEAE revealed rich chemical profile of 28 compounds, dominated by flavones namely, naringenin, trihydroxy-dimethoxy flavone, dihydroxy-trimethoxy flavone. Among others, glycosides such as clerodendrin, calceolarioside E, forsythoside B, geniposide, martynoside and glucuronides such as, luteolin-7-diglucuronide, tricin-7-O-glucuronide, luteolin-7-O-glucuronide were also identified. LEAE exhibited exceptionally high in-vitro (LC50 = 6900 ppm) and in-vivo (computed as damage score on a scale of 1-9) insecticidal activity against S. frugiperda; with no phytotoxicity at dose as high as 20 times of LC50. LEAE also exhibited significant antifeedant, ovicidal and growth regulatory activity at 70-16000 ppm (w/v) concentration range. In-silico assessment revealed strong binding of martynoside, calceolarioside E, and forsythoside B with acetylcholinesterase, sodium and chloride dependent γ-aminobutyric acid (GABA) receptor and ryanodine receptor, respectively; facilitated by hydrogen bonds (conventional and C-H bonds) stabilized by hydrophobic Pi-sigma, Pi-Pi stacked, Pi-Alkyl and Alkyl interactions.Present study established L. alba as a potential bioresource and secondary metabolite enriched LEAE as a potent bioinsecticide for further product development.